Parasitological investigation of children's sandboxes and dog faeces from public areas of housing development in Prague - Valkounová, J (Folia parasitologica, 1982)
Two hundred sand samples from 50 children's sandboxes and 500 samples of dog faeces collected in 10 Prague housing developments were examined for the presence of parasites. Eggs of three helminth species were found in 28% of sandboxes and eggs and oocysts of 10 species of parasites were found in 10.4% of dog faeces. Toxocara canis occurred in 9 sandboxes and 3.2% of dog faeces, T. cati in 0.2% of dog faeces. The results from housing developments are compared with those from older estates.
Keywords: Feces; Ovum; psi; Czechoslovakia; Dogs; Československo; Toxascaris; Nematoda; ovum; Toxocara; bydlení; ženské pohlaví; zvířata; feces; Soil; Housing; hra a hračky; hlístice; Strongyloides; Female; Play and Playthings; půda; Animals